Pengembangan E-Module Proyek Penguatan Profil Pelajar Pancasila Kelas IV Sekolah Dasar Pada Kurikulum Merdeka - Sonia Yulia Friska; Wiwik Okta Susilawati; Wahyu Nopriandi (Universitas Pahlawan Tuanku Tambusai, 2023)
This research was motivated by the difficulty of students understanding the steps of project activities, the difficulty of students with audio-visual learning styles to understand the material in the project module. This study aims to develop an e-module project to strengthen the profile of grade IV elementary school pancasila students in the independent curriculum. This type of research and development uses the type of Research and development (R&D) research. The e-module development model for the project to strengthen the profile of grade IV elementary school pancasila students in the independent curriculum uses the ADDIE development model (Analyze, Design, Deveploment, Implementation, and Evaluation). The five stages are carried out through needs analysis, student characteristics analysis, and curriculum analysis. Then the validation of the e-module project to strengthen the profile of grade IV elementary school pancasila students in the independent curriculum was validated by FKIP UNDHARI lecturers, practicality which was carried out by looking at teacher responses. The results of the development of the e-module project to strengthen the profile of grade IV elementary school pancasila students in the independent curriculum were declared very valid. Based on the results obtained from validators obtained with an average of 93.1% with a very valid category, the results of practicality with an average of 96% are categorized as very practical Thus, it can be concluded that the e-LKPD made is very valid, practical, for teachers to use in project activities.